Vergleich der Weiterbildungsaktivitäten von Arbeitslosen und Vollzeiterwerbstätigen - Birgit Schultz; Joachim Wilde (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
– Many empirical studies for Germany consider either the training activities of the unemployed or those of employees. However, a comprehensive comparison of both groups had not been conducted until now. The paper closes this gap. Using data from the latest time-use survey (Zeitbudgeterhebung) of the Federal Statistical Office, the amount of training undertaken by the two groups is compared. Furthermore, the types of activities that are made use of in particular are described. Heterogeneity due to different relevant socioeconomic characteristics in the two groups is eliminated by applying a matching procedure. The findings demonstrate that only 49 % of unemployed people participate in any kind of training activity off the job. In the case of full-time employment 59 % would take part. Concerning the average expenditure of time per week the difference is reversed, i. e. the expenditure of time is greater during unemployment. However, a large proportion of the training activities undertaken by the unemployed comprises general training, e. g. by reading books or watching television. Furthermore, the result is driven by a different potential of time that can be used for training activities off the job. In relation to this potential of time, the amount of training activity is still smaller during unemployment.
Keywords: 330; Weiterbildung; selbstgesteuertes Lernen; Bildungsbeteiligung; Arbeitslose; Erwerbstätige; Vollzeitarbeit; Zeitbudget; Zeitverwendung